Hub Genes, Diagnostic Model, and Predicted Drugs Related to Iron Metabolism in Alzheimer's Disease - Gu, Xuefeng; Lai, Donglin; Liu, Shuang; Chen, Kaijie; Zhang, Peng; Chen, Bing; Huang, Gang; Cheng, Xiaoqin; Lu, Changlian (Frontiers in Aging Neuroscience, 2022)
Although Alzheimer's disease (AD) is the most common neurodegenerative disease, the underlying causative genes and effective therapeutic approaches are unknown. Abnormalities in iron metabolism have been demonstrated in AD patients and AD mouse models. This study explored hub genes based on iron metabolism that can influence the diagnosis and treatment of AD. First, gene expression profiles were downloaded from the GEO database, including nondemented (ND) controls and AD samples. Fourteen iron metabolism-related gene sets were downloaded from the MSigDB database, yielding 520 iron metabolism-related genes. The final 9 hub genes associated with iron metabolism and AD were obtained by differential analysis and WGCNA in brain tissue samples from GSE132903. GO analysis revealed that these genes were mainly involved in two major biological processes, autophagy and iron metabolism. Through stepwise regression and logistic regression analyses, we selected four of these genes to construct a diagnostic model of AD. The model was validated in blood samples from GSE63061 and GSE85426 due to the difficulty of extracting brain tissue from patients, and the AUC values showed that the model had a relatively good diagnostic performance. In addition, the immune cell infiltration of the samples and the correlation of different immune factors with these hub genes were further explored. The results suggested that these genes may also play an important role in immunity. Finally, eight drugs targeting these nine hub genes were retrieved from the DrugBank database, some of which were shown to be useful for the treatment of AD or other concomitant conditions, such as insomnia and agitation. In conclusion, this model is expected to guide the diagnosis of AD patients by detecting the expression of several genes in the blood. These hub genes may also assist in understanding the development and drug treatment of AD.